Simultaneous determination of atenolol and chlorthalidone in pharmaceutical preparations by capillary-zone electrophoresis - Khaldun, Al-Azzam; Elbashir, Abdalla A.; Elbashir,, Mohammed A; Saad, Bahruddin; Abd Hamid, Shafida (Taylor & Francis Inc., 2009)
A capillary zone electrophoresis (CZE) method for the simultaneous determination of the β-blocker drugs atenolol and chlorthalidone in pharmaceutical formulations has been developed. The CZE separation was performed under the following conditions: capillary temperature, 25°C; applied voltage, 25 kV; 20 mM H3PO4–NaOH running buffer (pH 9.0); and detection wavelength, 198 nm. Phenobarbital was used as internal standard. The method was validated and showed not only good precision and accuracy but also good robustness. The method has been successfully applied to the simultaneous determination of both atenolol and chlorthalidone in pharmaceutical tablets.